Physical Growth in Children with Transfusion Dependent Thalassemia (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Thalassaemia is a major congenital hematological disease of Bangladesh. Poor growth and delayed maturation occurs in these patients commonly. This study was aimed to evaluate the physical growth in Transfusion Dependent Thalassemia (TDT).Materials and methods: This cross-sectional comparative study enrolled 60 diagnosed Children with Transfusion dependent Thalassemia over I year and carried out in Pediatric Hematology and Oncology unit and Hematology Department of Chittagong Medical College Hospital, Chattogram. Among them, 30 children received blood transfusion >12 times per year was considered as group I and rest 30 children received blood transfusion £12 times per year was considered as group II. Statistical analysis was done by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-22).Results: The mean serum ferritin was higher in group I than group II(1243.77±761.626 and 293.77±142.686 respectively). Almost two third (60.0%) patients were severely stunted in group I and 8(26.7%) in group II. 28(93.3%) patients had under weight (